Enhancing carbon dots fluorescence via plasmonic resonance energy transfer. (May 2022) - Sciortino, A.; Panniello, A.; Minervini, G.; Mauro, N.; Giammona, G.; Buscarino, G.; Cannas, M.; Striccoli, M.; Messina, F.
Highlights: Enhancement of red emission of carbon nanodots by plasmonic resonance energy transfer. Ultrafast spectroscopic investigation on plasmonic resonance energy transfer. Spectroscopic study of carbon nanodots- Gold nanoparticle composite by ultrafast pump probe measurements. Abstract: Using plasmonic interactions to engineer optical properties at the nanoscale is an important challenge of current photonics. Here we establish a general strategy to enhance the orange emission of carbon dots by coupling them to gold nanoparticles through a polymeric spacer in solution. We exploit the overlap between the surface plasmon resonance of gold and the electronic transitions of carbon dots to achieve a fivefold increase of their fluorescence in the orange region, which is usually very weak. We demonstrate that this enhancement stems from an ultrafast resonance energy transfer from the coherent plasmonic state of the gold nanoantenna to the coupled carbon dot. Our study advances the understanding of the fundamental interactions between fluorescent and plasmonic nanomaterials. Furthermore, the results contribute to address a pressing challenge in the field of carbon dots, promising a significant impact on their technological use in optoelectronics and bioimaging. Graphical abstract: Image, graphical abstract